Opini Lirik “Gala Bunga Matahari” Lagu Sal Priadi - Wijaya, Edi; Sejati, Taqwa; Wulandari, Sri (AL-MIKRAJ Jurnal Studi Islam dan Humaniora (E-ISSN 2745-4584), 2024)
Nowadays, song lyrics have become an expression of the writer's heart which is then sung by singers with a certain style and distinctive characteristics. The song then becomes a 'prayer' from the writer for the listener, which invites the listener to feel love and joy and also undeniably invites a feeling of sadness together. This research is a type of qualitative descriptive research which uses a communication science approach, specifically focusing on mass communication, one of the objects of research is the lyrics in question. Meanwhile, the data collection method used in this research is Ferdinand Saussure's semiotic theory, observation is also of course documentation to strengthen and serve as authentic evidence. Meanwhile, the sources for this research also come from the researcher's book, search results from several research supporting articles on confirmed website pages as well as supporting documents both outside the network and on other networks. The next step is for the collected data to be immediately analyzed. The results of the analysis are data education regarding the theory used, explanation and conclusions